Proposed programmed material in reading for grade six pupils - Faz, Edna Ferrancullo 1941- (1977)
This study is an attempt to prepare programmed material in reading for grade six pupils. This study aimed further to provide teachers with exercises for developing three basic reading skills and thinking processes. The passages were culled from different sources, among which were prescribed grade six textbooks, supplementary readers, magazines, Readers Digests, and other materials. This programmed material was tried out in the form of a test to 180 grade six pupils enrolled during the school year 1976-1977 at the Odiongan South Central School. The test was used to evaluate the significance of the difference between posttest and pretest means. The programmed material is expected to be done by the pupils at their own rate with minimum help from the teacher who supervises activities and evaluates learning performance. A manual for teachers has been prepared for future uses of the material, but it should not be used to the exclusion of other diagnostic tools.
"May, 1977."
Vita.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Reading (Elementary) -- Philippines -- Odiongan (Romblon); Reading comprehension -- Programmed instruction